Education for Sustainable Development from the Perspective of Mieczysław Gogacz's Realistic Pedagogy - Agnieszka Klimska (The Francis de Sales Scientific Society (TNFS.PL), 2021)
In the face of the "weakness of indicators" of the progress in the implementation of the postulates of sustainable development, opinions appear about "the depletion of the paradigm of sustainable development". So far, strengthening the practice of sustainable development, involved, among others, implementation of education for sustainable development. However, certain omissions have been revealed in the area of educational activities. education. Taking into account these failures, it seems that it is worth "humanizing" education. The article is an attempt to embed education for sustainable development in the realistic pedagogy of M. Gogacz, built on the basis of consistent Thomism.